Analysis of Teacher Pedagogical Competence Policy in the Digital Era at SMPN 2 Mataram - Muhammad Muhsin Al-Anshari (al-Afkar, Journal For Islamic Studies, 2026)
The digital era has brought fundamental changes to the education system, requiring teachers to possess pedagogical competencies that are adaptive to developments in information technology. This study aims to analyze policies for developing teacher pedagogical competencies to improve the quality of learning in the digital era, with a focus on their implementation at SMP Negeri 2 Mataram. The research approach used descriptive qualitative methods through literature studies, observations, and interviews with teachers and school leaders. The results show that government policies such as the Teacher Mover Program, Teacher Professional Education (PPG), and the Merdeka Mengajar Platform have made a positive contribution to improving teacher pedagogical competencies. Teachers at SMP Negeri 2 Mataram demonstrated improved capabilities in planning, implementing, and evaluating digital technology-based learning. However, policy implementation still faces challenges such as limited digital infrastructure, technological literacy gaps among teachers, and high administrative burdens. Efforts to strengthen policies and ongoing support from schools and local governments are essential to ensure the sustainability of digital-based pedagogical competency development. This research contributes to providing an empirical overview of the implementation of policies for developing teacher pedagogical competencies at the junior high school level in the digital era, while also providing strategic recommendations for schools and policymakers in optimizing the use of technology to improve learning quality. This research emphasizes the importance of synergy between national policies, school management, and teacher initiatives to create effective, innovative, and relevant learning for the needs of the 21st century.